2017
DOI: 10.1530/rep-16-0473
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional signatures throughout development: the effects of mouse embryo manipulation in vitro

Abstract: Stressful environmental exposures incurred early in development can affect postnatal metabolic health and susceptibility to non-communicable diseases in adulthood, although the molecular mechanisms by which this occurs have yet to be elucidated. Here we use a mouse model to investigate how assorted in vitro exposures restricted exclusively to the preimplantation period affect transcription both acutely in embryos and long-term in subsequent offspring adult tissues, to determine if reliable transcriptional mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 84 publications
(103 reference statements)
1
22
0
Order By: Relevance
“…As some metabolites stemmed from the metabolism of arachidonic acid were here detected down-accumulated in FT and VT embryos, it could explain its lower survival rates compared to the NC ones. It is worth noting that some of the metabolic changes here described have also been reported in adult tissues of ART animals [ 13 , 46 , 47 , 48 ]. Therefore, the study of the molecular changes occurring in the preimplantation embryo after ART could provide a set of compounds that can serve as metabolic markers to better understand and track those deviations that appear both in the short and in the long term.…”
Section: Discussionsupporting
confidence: 55%
“…As some metabolites stemmed from the metabolism of arachidonic acid were here detected down-accumulated in FT and VT embryos, it could explain its lower survival rates compared to the NC ones. It is worth noting that some of the metabolic changes here described have also been reported in adult tissues of ART animals [ 13 , 46 , 47 , 48 ]. Therefore, the study of the molecular changes occurring in the preimplantation embryo after ART could provide a set of compounds that can serve as metabolic markers to better understand and track those deviations that appear both in the short and in the long term.…”
Section: Discussionsupporting
confidence: 55%
“…Schwarzer et al () also analyzed the mouse blastocyst transcriptome, showing that different culture conditions induced greater differences in gene expression than different paternal genotypes, and that differentially expressed genes induced by IVC were involved in metabolism. In a comprehensive transcriptional analysis, Feuer et al () addressed the effect of the fertilization method, culture medium, and oxygen tension on the transcriptome of blastocysts. ICSI induced the highest number of differentially expressed genes among fertilization procedures, and Whitten’s medium at 20% oxygen was the most stressful culture condition (Feuer et al, ).…”
Section: Embryonic Responses To Art‐induced Stress In the Mouse Modelmentioning
confidence: 99%
“…In a comprehensive transcriptional analysis, Feuer et al () addressed the effect of the fertilization method, culture medium, and oxygen tension on the transcriptome of blastocysts. ICSI induced the highest number of differentially expressed genes among fertilization procedures, and Whitten’s medium at 20% oxygen was the most stressful culture condition (Feuer et al, ). We compared embryo development and global gene expression in embryos cultured in vitro in KSOM supplemented or not with fetal calf serum (FCS) and in vivo collected embryos (Fernández‐González et al, ).…”
Section: Embryonic Responses To Art‐induced Stress In the Mouse Modelmentioning
confidence: 99%
“…Considerable dysregulation in gene expression was observed both in embryos and adult tissues. Although no obvious pathway could be identified linking IVP embryos and adult tissues derived from embryos in the same in vitro conditions, some common regulators were identified in embryos and somatic tissues in some of the tested IVP conditions (Feuer et al, ). In another study, increased glucocorticoid receptor (GR) expression was observed in inbred and outbred mouse IVP blastocysts cultured in KSOM.…”
Section: Long‐term Effects Of Artmentioning
confidence: 99%
“…One of the most comprehensive analysis was performed by Feuer et al () compiling several studies led by Rinaudo's laboratory and addressing the effect of different culture medium composition, oxygen tension during culture and fertilization method on blastocyst transcriptome. Two subsets of data were analyzed.…”
Section: Effects Of Art Process On Early Embryo Developmentmentioning
confidence: 99%